Effectiveness of Brief Behavioral Activation for Improving Social Connectedness in Lonely Older Adults - Rizky Amellia; Yanto Prasetyo (Kirana Publisher (KNPub), 2026)
Loneliness among older adults is a common psychosocial problem that negatively affects social Loneliness among older adults is a common psychosocial problem that negatively affects emotional well-being, social connectedness, and quality of life. This condition is often worsened by the loss of a spouse, limited daily activities, and reduced meaningful social interactions. This study aimed to examine the effectiveness of Brief Behavioral Activation for Improving Social Connectedness (BBAISC) in reducing loneliness and enhancing social connectedness. A pre-experimental Single Case Experimental Design (pretest–posttest) was used with a 60 year old woman who experienced loneliness after losing her spouse and had limited social support. The participant was selected purposively. Data were collected through participant interviews, interviews with a community health volunteer, behavioral observation, the UCLA Loneliness Scale, the 16 Personality Factors (16PF) Test, and graphic tests (DAP and BAUM). The intervention consisted of six weekly individual sessions, including guided discussions, identification of personal values, activity monitoring and scheduling, gradual social activation, strengthening social support, and evaluation of behavioral changes. Quantitative data were analyzed using the Wilcoxon Signed-Rank Test due to non-normal distribution. Results showed a significant reduction in loneliness from pretest to posttest (Z = −2.830; p = 0.005). This study concludes that BBAISC is an effective and practical psychosocial intervention for reducing loneliness and improving social connectedness among older adults.